Application of Analytical Techniques in Preformulation Study: A Review - Kirtansinh, Gohil (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Analytical techniques are fundamental to Preformulation Studies. Without them, no evaluation of the quality of materials, product precursors, or final product can be made. No biological or pharmacologic responses in the preclinical or clinical stages can be measured. Selection of analytical techniques should be based on the elements of the study; specificity, accuracy, precision, sensitivity, and speed of a test must be justified for the method selected. To generate Preformulation data analytical techniques like Spectroscopic, Chromatographic, Thermal methods and some specific detection methods like Capillary electrophoresis are used. The present article is framed with the objective to provide an in-depth insight the application of Analytical Techniques in Preformulation Study.Key word: Preformulation Study, Thermal Methods, Capillary electrophoresis, Precursors